A RETROSPECTIVE COHORT OF VITAMIN D DEFICIENCY ANALYSIS AND GLYCATED HEMOGLOBIN (HBA1C) LEVELS ASSOCIATIONS IN TYPE 2 DIABETES MELLITUS PATIENTS (The Research of Medical Science Review, 2025)
The prevalence of type II diabetes mellitus (T2DM) is reported to be alarmingly high in Pakistan. According to different reports, hyperglycemia is associated with low vitamin D levels. The main objective of this research is to evaluate the association between vitamin D levels and HbA1c% (glycated hemoglobin) in enrolled participants with T2DM. The current retrospective and cohort study was conducted on 253 T2DM patients aged over 18 years. The proposed questionnaire included attributes like medical records, demographic data, and diagnosis of T2DM. The figures obtained were analyzed using SPSS software (Statistical Package for the Social Sciences). Of enrolled 253 patients, 185 patients aged 45-60 exhibited mean HbA1c% 8.28% (SD value +1.327), and the mean 25-OH vitamin D3 level was less than 20 ng/ml. Our study reported Pearson’s correlation coefficient (r = -0.348) between HbA1c% and 25-OH vitamin D3 levels. The findings of this study indicate a negative correlation between vitamin D levels and HbA1c% among patients with T2DM. Using vitamin D supplements in conjunction with diabetes therapy may be an effective preventive strategy to minimize the complications associated with the diabetic condition.